Influence of the addition of polyethylene terephthalate to improve compressive strength and its mechanical properties in masonry units (SCIÉNDO INGENIUM, 2024)
The objective of this study was to determine the resistance acquired with the incorporation of recycled PET into masonry units, in addition to knowing its mechanical properties, to determine the mechanical properties of the masonry system. Optimal proportions of aggregates were determined in the concrete mix to make class IV masonry unit. Subsequently, PET plastic mortar was added to the mixture, using an extruder with a percentage of 0%., 5%, 10%, 15%, 20% and 25%, adding recycled material, with compression resistance being its most influential property, the determined characteristic values ​​are f'b = 126.60 kg/cm2, f'b = 120.77 kg/cm2, f'b =115.93 kg/cm2, f'b = 115.93 kg/cm2, f'b = 112.87 kg/cm2, f'b = 108.85 kg/cm2 and f'b = 106.09 kg/cm2 for percentages of 0%, 5%, 10%, 15%, 20%, 25% PET, respectively. It was determined that the greater the amount of PET-type plastic incorporated, the compressive strength decreases, although another property such as warping or moisture absorption, comply with the E.070:2006 standard, the six types of concrete bricks - PET (0%, 5%, 10%, 15%, 20%, 25% PET) according to their properties they are classified as Class IV brick, and can be used structurally.
Keywords: Masonry unit; PET recycling; endurance; extruder; NTP E0.070